Implementasi Nilai – Nilai Pancasila dalam Penegakan Hukum Pidana terhadap Tindak Pidana Korupsi - Ashfiya Nur Atqiya; Ahmad Muhammad Mustain Nasoha; Salma Azzahra; Raihan Mukhtar Bairani Putra; Rifqy Luthfi Amalia; Dzaky Adam Maulana (Jurnal Hukum dan Sosial Politik, 2024)
Enforcement of criminal law against criminal acts of corruption in Indonesia requires an approach that is not only based on positive legal provisions but also reflects the values ​​of Pancasila as the basis of the state. Pancasila, with five principles covering aspects of Divinity, Humanity, Unity, Democracy and Social Justice, provides the moral and ethical framework that underlies legal principles in Indonesia. This research aims to explore how Pancasila values ​​are applied in enforcing criminal law against corruption, as well as the challenges and obstacles faced in the implementation process. By using an analytical approach to legal literature and current case studies, this research finds that the application of Pancasila values ​​can increase integrity, transparency and justice in the legal system. Nonetheless, issues such as a widespread culture of corruption, deficiencies in the legal system, and a lack of collaboration among agencies present major challenges. This study suggests overhauling the legal system, enhancing education and training for law enforcement personnel, and promoting community engagement to better implement Pancasila values in the enforcement of criminal laws against acts of corruption.